Economic Complexity and National Culture: An Analysis from the Perspective of Income - de Lima, Manuella Aparecida Felix [UNESP]; Crepaldi, Antonio Fernando [UNESP] (FapUNIFESP (SciELO), 2024)
The different characteristics of the cultural dimensions of a country give rise to different collective behaviors that impact the way of living, the organization of work and the economy. This study investigated the correlations between the cultural dimensions according to Hofstede (power distance, individualism-collectivism, masculinity-femininity, uncertainty avoidance, long-term orientation and indulgence-restraint) and the countries’ economic complexity indexes. A canonical correlation analysis was performed to determine the magnitude of the relationships between the two sets of variables. The results revealed significant correlations between culture and complexity, varying according to the countries’ income. Cultural characteristics such as lower power distance, greater individualism and greater indulgence were associated with more complex economies, based on innovation and scientific research. Masculinity-femininity and uncertainty avoidance did not show a significant correlation. Greater long-term orientation correlated with more export-diversified economies. These conclusions can guide more effective development policies, respecting cultural particularities.
Complexidade econômica e cultura nacional: uma análise sob a perspectiva da renda
Keywords: correlation; cultural dimensions; economic complexity; income classification; national culture